KOMUNIKASI SPIRITUAL PASIEN PENDERITA LUPUS DI KOTA BANDUNG - Titih Nurhaipah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Communication based on subjectivity related to the importance of pain suffered by patients with lupus to carry the disease implies self-spirituality with God as an interaction. The method used in this study are phenomenological studies that reveal phenomena based on the subjective experience of patients with lupus. Its objective is to discover the form of spiritual communication made by patients with lupus and the meaning they have. The results of this study are prayer as a form of spiritual communication and the meaning of the illness understood emotionally, spiritually and physically. Keywords: communication, spirituality, patients with lupus.